complete socialization about vaginal discharge or fluor albus at SMK Bina Jaya Palembang in 2021: Socialization - Atma Deviliawati (Khidmah, 2021)
Adolescence is defined by growth, change, and the presence of new chances, and it is often associated with reproductive health problems. In teenage girls, reproductive organ healthcare is expected to prevent significant problems. Preventing vaginal discharge or fluor albus is one of the aims of treatments of reproductive organs in teenage girls. Vaginal discharge or fluor albus is a discharge from the tiny glands in the vagina and cervix that may or may not smell and lead to a local itching. The causes of vaginal discharge or fluor albus may be normal or physiologic. According to 2012 data from the Indonesian Demographic and Health Survey (IDHS), around 18% of women aged 15-49 years had encountered the vaginal discharge or fluor albus. This socialization has the objective of educating teenage girls about vaginal discharge or fluor albus. The strategy is to provide direct socialization through counseling and leaflet distribution, while also following the health protocols. The activity occurred on july 12, 2021. The results of the socialization obtained data on knowledge about vaginal discharge or fluor albus from 46 students before being given socialization with good knowledge of 15 people (32.6%) and after the socialization, there was an increase in students with good knowledge of vaginal discharge or fluor albus as many as 44 students ( 95.7 percent ). Proves an increase in awareness of vaginal discharge or fluor albus before and after socialization. Suggestions for educators to regularly educate students about reproductive health, either in cooperation with health education organizations or with other health authorities.